Distinct perception profiles of gig economy employment among nursing students in Saudi Arabia: a latent profile analysis - Alya Alghamdi; Bandar S. Alharbi; Majed M. Aljabri (Frontiers in Medicine, 2026)
Background The gig economy has become an innovative employment model with the potential to enhance workforce flexibility and support healthcare delivery. However, concerns regarding employment security, professional regulation, and continuity of care remain. Understanding how future nurses perceive this evolving employment model is important because these perceptions may influence future career decisions and the adoption of flexible workforce strategies. This study aimed to identify distinct latent profiles of nursing students based on their perceptions of gig economy employment and to examine factors associated with profile membership. Methods We performed a cross-sectional survey among undergraduate nursing students in four public universities in Riyadh, Saudi Arabia. All eligible undergraduate nursing students who registered during the study period were invited to participate. Data were collected using a structured self-administered questionnaire. The questionnaire assessed nursing challenges, gig economy characteristics, gig economy perceptions, perceived benefits, and perceived impact. Model selection was based on information criteria, entropy, the bootstrap likelihood ratio test (BLRT), profile size, and interpretability. Multinomial logistic regression was performed to identify factors associated with latent profile membership. Results A total of 291 nursing students were included in the analysis. Although the four-profile solution showed slightly better information criteria and higher entropy, these improvements were modest and were accompanied by increased model complexity. Considering the overall balance between statistical fit, profile size, parsimony, and substantive interpretability, the three-profile solution was selected for subsequent analyses, comprising Gig Economy Enthusiasts (39.2%), Pragmatic Evaluators (37.8%), and Personal Impact-Oriented Supporters (23.0%). Compared to Gig Economy Enthusiasts, higher perceived nursing challenges were significantly associated with increased odds of belonging to the Pragmatic Evaluators profile (OR = 2.12, 95% CI: 1.23 to 3.67). Nationality, age, and sex were not significantly associated with membership in this profile. Similarly, higher nursing challenge scores were independently associated with membership in the Personal Impact-Oriented Supporters profile (OR = 2.48, 95% CI: 1.31 to 4.69). Conclusion Nursing students showed heterogeneous perceptions of gig economy employment, with three distinct attitudinal profiles identified. The findings highlight the importance of incorporating flexible employment concepts into nursing education and workforce planning while addressing concerns related to nursing practice.